Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages INTRODUCTION The world has entered upon the most decisive year of the war, and in order to make this year a victorious one for us and our allies, we have to surpass ourselves in production. Workers' representatives and organizations are taking the lead to achieve this end. Health is a vitally important aspect of production. But how far has the problem of health been tackled by the workers? Through ordinary ill-health alone among the industrial workers, 29 million weeks' work is lost each year. This is equivalent to 9,000 fighter aircraft. This is how we must regard ill-health — in terms of how many planes, tanks, and guns do not get made because those whose job it is to make them are away sick. This pamphlet is designed to help all workers' organizations wishing to concern themselves with health matters. Although the information must be limited, it does contain many essential facts you should know concerning the legal requirements for factory hygiene and conditions, and for the prevention of accidents. And it suggests ways and means by which the organized workers may use these facts to improve their health and at the same time establish new records for production. The pamphlet does not cover all sections of the Factories Act, or deal with the special regulations which have been made for certain dangerous trades. A list of these regulations is given at the end in an appendix, together with the titles of other books and pamphlets which should be consulted on special subjects. INDUSTRIAL HEALTH COMMITTEE, LABOUR RESEARCH DEPARTMENT, 6 High Holborn, London, W.C.1 APRIL, 1942 21/2049